Head growth during neonatal intensive care unit stay is related to the neurodevelopmental outcomes of preterm small for gestational age infants - Hannah Cho; Ee-Kyung Kim; In Gyu Song; Ju Sun Heo; Seung Han Shin; Han-Suk Kim (Elsevier, 2021)
Background: To investigate postnatal growth patterns and their relationship with the neurodevelopment of preterm infants born small for gestational age (SGA). Methods: This retrospective cohort study analyzed 90 infants born SGA with a birthweight <1500 g or gestational age <32 weeks. Length, weight, and head circumference (HC) were recorded at birth, 35 weeks postmenstrual age (PMA), 40 weeks PMA, and 4, 9, and 18 months corrected age (CA). Neurodevelopmental outcomes were assessed using the Bayley-III scales at 18 months CA. Results: The Z-score of HC in SGA infants increased from birth to 40 weeks PMA. Failure of head growth catch-up to the 10th percentile by four months CA and all three parameters by nine months CA were associated with worse neurodevelopmental outcomes. Z-score changes in head growth between birth and 35 weeks PMA were significantly associated with neurodevelopmental outcomes (p = 0.006; adjusted odds ratio, 6.964; 95% confidence interval: 1.763-27.506). Conclusion: Head growth trajectory during neonatal intensive care unit stay is associated with neurodevelopmental outcomes in preterm SGA infants. If head growth catch-up is achieved by four months CA and length and weight catch-up by nine months CA, preterm SGA infants are predicted to have optimal neurodevelopment at 18 months CA.